The impact of conservation on the status of the world’s vertebrates - Hoffman, M. (2010)
Using data for 25,780 species categorized on the International Union for Conservation of Nature Red List, we present an assessment of the status of the world’s vertebrates. One-fifth of species are classified as Threatened, and we show that this figure is increasing: On average, 52 species of mammals, birds, and amphibians move one category closer to extinction each year. However, this overall pattern conceals the impact of conservation successes, and we show that the rate of deterioration would have been at least one-fifth again as much in the absence of these. Nonetheless, current conservation efforts remain insufficient to offset the main drivers of biodiversity loss in these groups: agricultural expansion, logging, overexploitation, and invasive alien species.